1977
DOI: 10.1161/01.cir.55.2.294
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of transiently ischemic from infarcted myocardium by serial imaging after a single dose of thallium-201.

Abstract: Myocardial 201Tl uptake and regional blood flow by the microsphere technique were determined in anesthetized dogs undergoing either 20 min of coronary occlusion and 100 min of reperfusion (N = 10) or 120 min of occlusion (N = 4). In both groups, 201Tl was injected intravenously after 10 min of occlusion. In transiently occluded dogs, regional flow at the time of 201Tl administration was reduced to 8 +/- 3% of normal flow in endocardial layers of the central ischemic zone. After 100 min of reperfusion, flow val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
88
0
5

Year Published

1979
1979
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 560 publications
(97 citation statements)
references
References 12 publications
4
88
0
5
Order By: Relevance
“…In contrast to exercise studies, which typically show a large increase in calculated double product, dipyridamole placed a much milder stress on the heart, which supports previous clinical observations of dipyridamole administration in catheterization studies.22 7 Nevertheless, 20% of the CAD patients had angina. This appeared to be related to the presence of multivessel CAD, as five of the 12 patients (42%) with threevessel disease had angina, compared with only three of 28 patients (1 1%) with one-and two-vessel disease (p < 0.01).…”
Section: Analysis Of Delayed Thallium-201 Distributionsupporting
confidence: 78%
“…In contrast to exercise studies, which typically show a large increase in calculated double product, dipyridamole placed a much milder stress on the heart, which supports previous clinical observations of dipyridamole administration in catheterization studies.22 7 Nevertheless, 20% of the CAD patients had angina. This appeared to be related to the presence of multivessel CAD, as five of the 12 patients (42%) with threevessel disease had angina, compared with only three of 28 patients (1 1%) with one-and two-vessel disease (p < 0.01).…”
Section: Analysis Of Delayed Thallium-201 Distributionsupporting
confidence: 78%
“…The use of the redistni bution kinetics of 201T1 for the performance of a singlo-dose rest and stress cardiac study has been studied by several investigators [7,12]. In one of these series, qualitatively, ‘¿ ‘¿ the nest images appeared similar to the 4â€"6 hr postexencise images previously obtained' ‘¿ [7].…”
Section: Discussionmentioning
confidence: 86%
“…It has been suggested that because of this continuous redistribution, if the tracer is administered during stress and permitted to redistribute itself while the subject is at rest, the delayed distribution will reflect perfusion at rest [7].…”
mentioning
confidence: 99%
“…Reversible defects correlate with myocardial ischemia as seen by dynamic ECG changes between resting and stress conditions. Likewise, defects observed in resting conditions can be reassessed with repeated delayed imaging (usually 3-4 h or 24 h later) for changes in signal intensity due to radiotracer redistribution (as described with thallium) (22,23). If the defect size decreases from rest to redistribution thallium SPECT (also termed ''fill-in'' or reversible defect), this signifies hypoperfused but viable myocardium (hibernation), which portends a high likelihood for recovery of function after revascularization (24).…”
Section: Radionuclide Cardiac Imagingmentioning
confidence: 99%